Pain therapy to reduce perioperative complications - Freys Stephan M.; Pogatzki-Zahn Esther (Innovative Surgical Sciences)
The incidence rates of adverse events secondary to any operation are a well-known problem in any surgical field. One outstanding example of such adverse events is postoperative pain. Thus, the incidence of acute postoperative pain following any surgical procedure and its treatment are central issues for every surgeon. In the times of Enhanced Recovery After Surgery (ERAS) programs, acute pain therapy became an increasingly well investigated and accepted aspect in almost all surgical subspecialties. However, if it comes to the reduction of postoperative complications, in the actual context of postoperative pain, surgeons tend to focus on the operative process rather than on the perioperative procedures. Undoubtedly, postoperative pain became an important factor with regard to the quality of surgical care: both, the extent and the quality of the surgical procedure and the extent and the quality of the analgesic technique are decisive issues for a successful pain management. There is growing evidence that supports the role of acute pain therapy in reducing postoperative morbidity, and it has been demonstrated that high pain scores postoperatively may contribute to a complicated postoperative course. This overview comprises the current knowledge on the role of acute pain therapy with regard to the occurrence of postoperative complications. Most of the knowledge is derived from studies that primarily focus on the type and quality of postoperative pain therapy in relation to specific surgical procedures and only secondary on complications. As far as existent, data that report on the recovery period after surgery, on the rehabilitation status, on perioperative morbidity, on the development of chronic pain after surgery, and on possible solutions of the latter problem with the institution of transitional pain services will be presented.